PERAN DISNEY COMPANY DALAM MENANAMKAN NILAI PEMBERDAYAAN PEREMPUAN MELALUI FILM MULAN - Sekar Anindya Radiansyah Puteri Puteri; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Mulan is one of the Disney Princess characters who successfully demonstrates gender equality and women empowerment as a women. Through her story, Mulan shows the audience, including those who are masculine and tough, unlike women in general. This shows that Mulan managed to break the stereotype that women have to be seductive, gentle, graceful, and obedient. Mulan's female leadership spirit has succeeded in inspiring the people who watched the film, especially women. SHE as a social group that engaged in podcasts calls on women that Mulan is an exemplary character because it shows gender equality and women's empowerment to their listeners because Mulan's character is more progressive than previous Disney characters Applying Constructivism Perspective and Feminism Theory as a reference for research, the author can explain how the shift in gender values that occurred in the Disney Princess film production related to the ongoing Feminism Wave and prove how women in Indonesia were inspired by the character Mulan to become a leader.. The research shows that Mulan's character is able to inspire society, especially for women in Indonesia to be aware of gender equality and also have a leadership spirit in women so that women in Indonesia can show their existence and are not easily oppressed by any group. Mulan, who works with men as colleagues, shows success in strengthening gender between men and women which can be implemented in everyday life. Keywords: Feminism, Women Empowerment, Gender Equality, Disney Princess